2008
DOI: 10.1159/000150601
|View full text |Cite
|
Sign up to set email alerts
|

Round Excisions Lead to Shorter Scars and Better Scar Positioning than Traditional Elliptical Excisions

Abstract: Background: As traditional elliptical excisions for skin tumors are designed before surgery, they may waste normal tissue and result in poor outcome, both in terms of the wound length and direction. Objective: To compare the predicted results of elliptical excisions with scars resulting from round excisions with dog ear repairs. Methods: Forty-one patients with skin tumors were prospectively studied. Each lesion was examined and an optimal ellipse was designed and marked on the skin. Only the lesion and the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
(12 reference statements)
0
9
0
1
Order By: Relevance
“…Although elliptical excision with a 3:1 length-to-width ratio is widely practiced in surgical practice, this technique may lead to unnecessary waste of normal tissue and longer scars (42). A prospective analysis of 41 patients undergoing elliptical and round excisions closed with dog ear repairs found that the overall wound length was 14% shorter for round excisions, most notably in the trunk, scalp, and other areas with thick skin (43). These findings are supported by additional reports of decreased scar length in punch compared to elliptical excisions (44,45).…”
Section: Wounds Outcomes and Scarringmentioning
confidence: 99%
See 1 more Smart Citation
“…Although elliptical excision with a 3:1 length-to-width ratio is widely practiced in surgical practice, this technique may lead to unnecessary waste of normal tissue and longer scars (42). A prospective analysis of 41 patients undergoing elliptical and round excisions closed with dog ear repairs found that the overall wound length was 14% shorter for round excisions, most notably in the trunk, scalp, and other areas with thick skin (43). These findings are supported by additional reports of decreased scar length in punch compared to elliptical excisions (44,45).…”
Section: Wounds Outcomes and Scarringmentioning
confidence: 99%
“…Although traditional elliptical excisions allow for primary closure with minimal risk for dog-ear deformity, the overall tissue loss and final scar length are suboptimal (42). Several other techniques, including round, punch, and staged excisions, may decrease the scar length while maintaining a low risk of dog-ear deformity (42)(43)(44)(45).…”
Section: Wounds Outcomes and Scarringmentioning
confidence: 99%
“…Seo et al [3] reported 14% shorter wounds compared to elliptical excisions and 12% of wounds being closed flat without need for dog ear repair. Twenty-two percent of wounds were closed in a different orientation to the original plan.…”
mentioning
confidence: 99%
“…The authors concluded that circular excision with dog ear repair, if necessary, could help achieve shorter and better‐oriented scars than traditional elliptical excision 15 . Seo and colleagues published a similar study in 2008 of 41 patients that found 14% shorter wound lengths, 22% with a change in direction, and 12% that did not require any dog ear repairs 16 …”
mentioning
confidence: 99%
“…15 Seo and colleagues published a similar study in 2008 of 41 patients that found 14% shorter wound lengths, 22% with a change in direction, and 12% that did not require any dog ear repairs. 16 A prospective study in 2004 attempted to remove benign-appearing papular nevi from the faces of 36 patients in a circular fashion. Cosmesis was rated as good to excellent in all patients, with only one of the 36 patients developing a dog ear.…”
mentioning
confidence: 99%